Interventions on military mobilities. (January 2017) - Merriman, Peter; Peters, Kimberley; Adey, Peter; Cresswell, Tim; Forsyth, Isla; Woodward, Rachel
Abstract: Mobility and movement are central to military actions and military life, and yet despite an increasing concern with military geographies and the geographies of mobility, little consideration has been given by scholars to the political geographies of military mobilities and movements, past or present. In these interventions, we examine how these different bodies of work might intersect, focusing on social media, methods for tracing military mobilities, the role of military technologies in facilitating everyday mobilities, and the more-than-human dimensions of military mobilities.